2009
DOI: 10.1002/mop.24609
|View full text |Cite
|
Sign up to set email alerts
|

A novel K‐shaped dual‐band antenna with a shorting pin for WLAN communications

Abstract: range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Latter, Choi [79] reported a novel K-shaped patch antenna for WLAN applications and measured gain ranging from 3.66 to 4.58 dBi. After then, Wang [80] described about the use of organic material as dielectric substrate for printed patch antenna in various wireless applications.…”
Section: Antenna Applicationsmentioning
confidence: 99%
“…Latter, Choi [79] reported a novel K-shaped patch antenna for WLAN applications and measured gain ranging from 3.66 to 4.58 dBi. After then, Wang [80] described about the use of organic material as dielectric substrate for printed patch antenna in various wireless applications.…”
Section: Antenna Applicationsmentioning
confidence: 99%
“…In practical applications, multiband microstrip antennas are preferred over single band antennas as they can be easily integrated in smart devices. Owing to techniques mentioned in other studies, 3–11 researchers have found ways to overcome the challenges of microstrip patch antenna with design of π‐shaped 12 and rhombus‐shaped antenna 13 ; multilayer structure using defected ground 14 ; K‐shaped design using shorting pin 15 and parasitically coupled L‐shaped stubs 16 for dual‐band operations; a Coplanar Waveguide (CPW)‐fed leaf‐shaped antenna with defected ground 17 ; circular patch with open‐ended elliptical shape ring slots and shorting vias 18 ; metamaterial‐based design loaded with meandered line and complementary split ring resonator (CSRR) 19 ; slots loaded bow‐tie patch with tapered ground 20 ; T‐shaped slot and slits‐loaded antenna 21 ; circular patch loaded with stub, slot, and V‐shaped slit 22 ; reconfigurable antenna using a pair of PIN diodes 23 ; and pentagonal shape ring slot with E‐shaped strip using partial ground 24 for triple‐band operation have been presented for different applications in wireless system. Frequency reconfiguration and multiple input multiple output (MIMO) technology has led to the revival of multiband and wideband operations in the field of wireless applications 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, a triple‐band stub and notches loaded compact antenna is intuitively conceived after going through the literature 1–16 and recently published triple‐band antennas 17–24 . The proposed design has triple‐band behavior in 1.40–2.13 GHz (lower band), 2.50–2.73 GHz (middle band) and 2.98–4.68 GHz (upper band) with impedance bandwidth ( S 11 < –10 dB) of 41.4% (730 MHz), 8.8% (230 MHz), and 44.4% (1700 MHz), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, compact E‐shaped and K‐shaped dual‐band microstrip antennas by using shorting pin for WLAN communications have been presented in Refs. [10] and [11], respectively. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna compared to dual‐band antennas with shorting pin reported in Refs. [10, 11] presents a simple structure for producing four frequency bands with good broadside radiation patterns and frequency tuning ability. The shorting pin in such schemes is utilized to excite a resonant frequency, which leads to a decrease in radiation efficiency, gain, and disturbance in radiation patterns.…”
Section: Introductionmentioning
confidence: 99%